TEMA Calidad De La Atención Y Estrategias De Detección Precoz De La Hipertrofia Prostática En Pacientes De 45 A 60 Años Asistidos En El Centro De Salud Tipo A “Hnos. Guevara” Del Cantón Pedro Carbo De La Provincia Del Guayas Durante El Periodo De Enero A Junio Del 2014 - Luiz Guanoluiza, Carlos Leonel (2015)
Written work contains a chapter I, INTRODUCTION where the problem formulation and justification of the study, research problem in Chapter II, defined. CONCEPTUAL THEORETICAL, discusses the theoretical framework related to the topic that describes the theoretical basis of our research, which has helped scientists identify and select content, to develop a proposal to develop a program QUALITY OF CARE AND STRATEGIES FOR EARLY DETECTION OF prostatic hypertrophy in patients 45 to 60 years attended at the CENTRO DE SALUD A " HNOS. GUEVARA " CANTON PEDRO CARBO of the province of Guayas DURING THE PERIOD FROM JANUARY TO JUNE 2014, these theoretical underpinnings applied in the respective field of work. Chapter III, METHODOLOGY where the methodology and techniques used in the field develops. Chapter IV, RESULTS OBTAINED, here the results are statistically present and have been timely porcentualizados, plotted, interpreted and discussed. Chapter V, CONCLUSIONS AND RECOMMENDATIONS presenting the achievements of the field work, previously synthesized and allows us to recommend and finally Chapter VI, PROPOSAL containing a proposed program to care for each of our users quality of care and strategies for early detection of prostatic hypertrophy in patients 45 to 60 years attended at the Type A Health Center "Guevara Brothers" of Pedro Carbo town in the Guayas province during the period from january to june 2014.